Factores de crecimiento empresarial en las microempresas productoras de lácteos del cantón Latacunga, parroquia Mulaló - Gutierrez Shigui, Evelyn Nataly (2017)
In this country, there are microenterprises that are created empirically, the same ones have generated employment for approximately 60 per cent of the (EAP) Economically Active Population in the Cotopaxi rural areas, thus improving the owners and their workers life quality. For this reason, the initiative to carry out this research about factors that prevent business growth in dairy products micro-enterprises producing at Latacunga Canton, Mulalo parish. Lack of growth factors influence the business development was the central problem, leading to this situation to the owners enter into a comfort zone and remain static without taking advantage of the opportunities that can be found in the environment. For this research project was framed as its main objective to determine the factors that hinder business growth on the basis of research based on bibliographic sources truthful, basing most content with regard to the proposed topic….